The expression of location and space in Surinamese and Indonesian Javanese - Villerius, Sophie (Wacana, Journal of the Humanities of Indonesia, 2018)
This paper examines the influence of language contact and multilingualism on the expression of location and space in the heritage variety of Javanese spoken in Suriname. Alongside Javanese, this community also speaks Sranantongo and Dutch. It is found that Surinamese speakers tend to use simple locative constructions more frequently than baseline speakers, at the expense of complex constructions. It is shown that the individual speaker variables age, generation, place of residence, and network play a role in explaining the usage of simple versus complex locative constructions in Surinamese Javanese: the more language contact speakers experience, the more they will use simple constructions at the cost of complex ones.